An Overview of Chinese Concepts of Family Through Traditional Values - Sema Gökenç Gülez (Şarkiyat Mecmuası)
This study aims to analyze and discuss family ethics, family structure, family members’ status and roles, the individual-family relationship, and the familystate relationship by analyzing the concept of family traditional values and norms within the framework of the theory of structural functionalism. Value judgments and normative rules in society are intensely experienced in the family as the smallest structural societal unit, and family ethics are important in terms of determining the functions and duties individuals have in the family as well as the relationship the family has with society and the state. Confucianism forms the basis of China’s traditional mentality and is based on family ethics, with individual, family, and state being considered inseparable concepts. For this reason, family ethics in Chinese society has been formed and shaped in line with the principles advocated by Confucianism. Although some changes have occurred in family structures and the status and roles of family members as a result of globalization and modernization, traditional values and their effects on the basis of family ethics in Chinese society can still be seen. This study compares certain aspects of family ethics with Western societies.